2002
DOI: 10.1124/mol.61.3.533
|View full text |Cite
|
Sign up to set email alerts
|

Channel Blockers Acting atN-Methyl-d-aspartate Receptors: Differential Effects of Mutations in the Vestibule and Ion Channel Pore

Abstract: A large number of structurally diverse compounds act as openchannel blockers of NMDA receptors. They may share discrete or overlapping binding sites within the channel. In this study, the effects of mutations in and around the membrane-spanning and pore-forming regions of NMDA receptor subunits were studied with three blockers, MK-801, memantine, and TB-3-4, using recombinant NMDA receptors expressed in Xenopus laevis oocytes. Mutations at the critical asparagine residues in the M2 loop of NR1 and NR2B and at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
182
3

Year Published

2003
2003
2008
2008

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 162 publications
(207 citation statements)
references
References 29 publications
22
182
3
Order By: Relevance
“…1A and B, 13A and B). Consistent with previous reports (Mori et al, 1992;Sakurada et al, 1993;Kawajiri and Dingledine, 1993;Ferrer-Montiel et al, 1995;Kashiwagi et al, 2002), we found that both the N616Q and N616R mutants decreased the affinity for MK-801. In sharp contrast, the N616 mutations did not affect the binding affinity of [ 3 H]DX suggesting that this ligand does not derive binding energy from the interaction with N616.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…1A and B, 13A and B). Consistent with previous reports (Mori et al, 1992;Sakurada et al, 1993;Kawajiri and Dingledine, 1993;Ferrer-Montiel et al, 1995;Kashiwagi et al, 2002), we found that both the N616Q and N616R mutants decreased the affinity for MK-801. In sharp contrast, the N616 mutations did not affect the binding affinity of [ 3 H]DX suggesting that this ligand does not derive binding energy from the interaction with N616.…”
Section: Discussionsupporting
confidence: 93%
“…Disruptive mutation of N650, a putative residue of the extracellular vestibule, reduced the affinity for both [ 3 H]MK-801 and [ 3 H]DX approximately four-to fivefold. Consistent with our results, a shift of the MK-801 IC 50 value from 2 nM to 13 nM for blockade of glutamate-induced currents has been reported for NR1-1a (N650A)/NR2B receptors (Kashiwagi et al, 2002). Since substitution at N650 does not entirely eliminate the binding of either [ 3 H]MK-801 or [ 3 H]DX, it is reasonable to propose that the residue is either a site of interaction for both ligands or confers topology to the pore/vestibule region that influences the affinity of both ligands.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations